Common Variant Near HEY2 Has a Protective Effect on Ventricular Fibrillation Occurrence in Brugada Syndrome by Regulating the Repolarization Current. (January 2016) - Nakano, Yukiko; Ochi, Hidenori; Onohara, Yuko; Toshishige, Masaaki; Tokuyama, Takehito; Matsumura, Hiroya; Kawazoe, Hiroshi; Tomomori, Shunsuke; Sairaku, Akinori; Watanabe, Yoshikazu; Ikenaga, Hiroki; Motoda, Chikaaki; et al.
Abstract : Background—: Risk stratification of Brugada syndrome (BrS) remains controversial and the majority of patients with BrS have no genetic explanation. We investigated relationships between genotypes of 3 single-nucleotide polymorphisms reported in a recent genome-wide association study and BrS phenotypes. Methods and Results—: SCN10A (rs10428132), SCN5A (rs11708996), and downstream from HEY2 (rs9388451) single-nucleotide polymorphisms were genotyped and compared between 95 Japanese patients with BrS and 1978 controls. Relationships between the single-nucleotide polymorphisms and clinical characteristics, 12-lead ECG findings, signal-averaged ECG findings, and electrophysiological parameters were also examined in patients with BrS. Both rs10428132 and rs9388451 were significantly associated with BrS ( P =2.7×10 −14 ; odds ratio, 3.0; P =9.2×10 −4 ; odds ratio, 1.7, respectively). Interestingly, the HEY2 risk allele C was less frequent in BrS patients with ventricular fibrillation than in those without (59% versus 74%; P =4.1×10 −2 ; odds ratio, 0.5). A significant linear correlation was found between HEY2 genotypes and QTc interval (CC: 422±27 ms; CT: 408±21 ms; and TT: 381±27 ms; P = 4.0×10 −4 ). The HEY2 mRNA expression level in the right ventricular specimens from patients with BrS (n=20) was significantly lower in patients with CC genotype than the other genotypes ( P =0.04). Additionally, during 63±28 months follow-up periods after implantable cardioverter defibrillator implantation (n=90), Kaplan–Meier event-free survival curves revealed that the cumulative rate of ventricular fibrillation events was significantly lower in cases with HEY2 CC genotype ( P =0.04). Conclusions—: Our findings suggest that HEY2 CC genotype may be a favorable prognostic marker for BrS, protectively acting to prevent ventricular fibrillation presumably by regulating the repolarization current.